Frozen in Translation: Biobanks as a Tool for Cancer Research - Martins, Ana Teresa; Carneiro, Isa; Monteiro-Reis, Sara; Lobo, João; Luís, Ana; Carmen Jerónimo, Carmen; Henrique, Rui (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
In the context of translational cancer research, biobanks are key infrastructures that provide high quality biological samples, coupled with relevant clinical and pathological information. This role can only be successfully accomplished through the implementation of standardized procedures that ensure proper collection, handling, processing, storage and recording of tissue samples, following strict legal and ethical regulations. Biobank networking is fundamental for dissemination of good practices and to help in the establishment of new infrastructures that improve the assessment of heterogeneity among tumor types and across patient cohorts. Growing demands for large number of homogenously preserved tumor tissue samples can only be met through a more intense cooperation among biobanks, facilitated by networks that foster cooperation at international level. The potential of biobanks as fundamental tools for translational cancer research can only be achieved through a concerted effort from biobankers, researchers, legislators and tissue donors that may allow for improved sample exchange.